Regulation of the instantaneous inward rectifier and the delayed outward rectifier potassium channels by Captopril and Angiotensin II via the Phosphoinositide-3 kinase pathway in volume-overload-induced hypertrophied cardiac myocytes - Alvin, Zikiar (International Scientific Literature, Inc., 2011)
BACKGROUND: Early development of cardiac hypertrophy may be beneficial but sustained hypertrophic activation leads to myocardial dysfunction. Regulation of the repolarizing currents can be modulated by the activation of humoral factors, such as angiotensin II (ANG II) through protein kinases. The aim of this work is to assess the regulation of I(K) and I(K1) by ANG II through the PI3-K pathway in hypertrophied ventricular myocytes. MATERIAL/METHODS: Cardiac eccentric hypertrophy was induced through volume-overload in adult male rats by aorto-caval shunt (3 weeks). After one week half of the rats were given captopril (2 weeks; 0.5 g/l/day) and the other half served as control. The voltage-clamp and western blot techniques were used to measure the delayed outward rectifier potassium current (I(K)) and the instantaneous inward rectifier potassium current (I(K1)) and Akt activity, respectively. RESULTS: Hypertrophied cardiomyocytes showed reduction in I(K) and I(K1). Treatment with captopril alleviated this difference seen between sham and shunt cardiomyocytes. Acute administration of ANG II (10(−6)M) to cardiocytes treated with captopril reduced I(K) and I(K1) in shunts, but not in sham. Captopril treatment reversed ANG II effects on I(K) and I(K1) in a PI3-K-independent manner. However in the absence of angiotensin converting enzyme inhibition, ANG II increased both I(K) and I(K1) in a PI3-K-dependent manner in hypertrophied cardiomyocytes. CONCLUSIONS: Thus, captopril treatment reveals a negative effect of ANG II on I(K) and I(K1), which is PI3-K independent, whereas in the absence of angiotensin converting enzyme inhibition I(K) and I(K1) regulation is dependent upon PI3-K.